Physiotherapy in Parkinson’s Disease: A Meta-Analysis of Present Treatment Modalities - Radder, Danique L. M. (Neurorehabil Neural Repair, 2020)
BACKGROUND: Physiotherapy is a commonly prescribed intervention for people with Parkinson’s disease (PD). Conventional types of physiotherapy have been studied extensively, while novel modalities are being developed and evaluated. OBJECTIVE: To evaluate the effectiveness of conventional and more recent physiotherapy interventions for people with PD. The meta-analysis performed as part of the 2014 European Physiotherapy Guideline for PD was used as the starting point and updated with the latest evidence. METHODS: We performed a systematic search in PubMed, CINAHL, Embase, and Web of Science. Randomized controlled trials comparing any physiotherapy intervention with no intervention or sham treatment were included. Trials were classified into 12 categories: conventional physiotherapy, resistance training, treadmill training, strategy training, dance, martial arts, aerobic exercises, hydrotherapy, balance and gait training, dual tasking, exergaming, and Nordic walking. Outcomes included motor symptoms, balance, gait, and quality of life, and are presented as standardized mean differences. The GRADE (Grading of Recommendations, Assessment, Development and Evaluation) approach was used to systematically appraise methodological quality. RESULTS: A total of 191 trials with 7998 participants were included. Conventional physiotherapy significantly improved motor symptoms, gait, and quality of life. Resistance training improved gait. Treadmill training improved gait. Strategy training improved balance and gait. Dance, Nordic walking, balance and gait training, and martial arts improved motor symptoms, balance, and gait. Exergaming improved balance and quality of life. Hydrotherapy improved balance. Finally, dual task training did not significantly improve any of the outcomes studied. CONCLUSIONS: This meta-analysis provides a comprehensive overview of the evidence for the effectiveness of different physiotherapy interventions in the management of PD, allowing clinicians and patients to make an evidence-based decision for specific treatment modalities. Further work is needed to directly compare the relative efficacy of the various treatments.